2007
DOI: 10.1007/s11136-007-9272-7
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis: a useful technique to identify elderly cardiac patients at risk for poor quality of life

Abstract: The cluster analysis was useful to identify the subgroup with poorer recovery. Patients in the Weary group need more attention and intervention strategies to improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 23 publications
2
45
0
2
Order By: Relevance
“…Kondisi ini justru dapat memicu timbulnya distres baru, ditambah lagi perubahan dalam kondisi fisik dan perubahan peran yang terjadi akibat sakit yang berkepanjangan. Beberapa penelitian mengungkapkan bahwa stress, depresi, rendahnya dukungan sosial dan spiritual dapat meningkatkan perburukan kondisi penyakit pada pasien dengan PJK (Aldana et al, 2006;Fukuoka, Lindgren, Rankin, Cooper, & Carroll, 2007;Davidson et al, 2013). Dan beberapa penelitian lainnya mengungkapkan masih tingginya angka cemas dan depresi pada pasien PJK di Indonesia (Krisnayanti, ;Widiyanti, 2013) sehingga komplikasi dan perburukan pun kemungkinan jumlahnya cukup tinggi.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kondisi ini justru dapat memicu timbulnya distres baru, ditambah lagi perubahan dalam kondisi fisik dan perubahan peran yang terjadi akibat sakit yang berkepanjangan. Beberapa penelitian mengungkapkan bahwa stress, depresi, rendahnya dukungan sosial dan spiritual dapat meningkatkan perburukan kondisi penyakit pada pasien dengan PJK (Aldana et al, 2006;Fukuoka, Lindgren, Rankin, Cooper, & Carroll, 2007;Davidson et al, 2013). Dan beberapa penelitian lainnya mengungkapkan masih tingginya angka cemas dan depresi pada pasien PJK di Indonesia (Krisnayanti, ;Widiyanti, 2013) sehingga komplikasi dan perburukan pun kemungkinan jumlahnya cukup tinggi.…”
Section: Pendahuluanunclassified
“…Pasien dengan PJK secara fisik mengalami berbagai perubahan yang dapat berpengaruh terhadap aspek lainnya seperti aspek psikologis dan spiritual. Secara fisik pasien dapat mengalami angina, sesak, mudah lelah serta gangguan seksual (Rosidawati et al, 2015) dan secara psikologis pasien dengan PJK sering mengalami cemas dan depresi (Aldana et al, 2006;Fukuoka, Lindgren, Rankin, Cooper, & Carroll, 2007;Davidson et al, 2013), lebih lanjut Sarafino dan Smith (2014) mengungkapkan bahwa masalah psikososial yang dialami oleh pasien dengan penyakit kronis adalah cemas, depresi, kemarahaan, dan keputusasaan. Cemas dan depresi yang dialami oleh pasien PJK menurut Amin, Jones, Nugent, Rumsfeld, dan Spertus (2006) dapat terjadi karena diagnosis dokter tentang penyakit serius, status kesehatan yang memburuk, intervensi pengobatan, dan kekambuhan gejala yang berulang.…”
Section: Pembahasanunclassified
“…Presence of symptoms, such as chest pain, fatigue, and shortness of breath affect HRQoL when patients recover acute cardiac events or procedures (Table 1). 33 Moreover, in coronary artery disease (CAD) patients, depressive symptoms and type D personality are independent predictors of poor HRQoL. People who show type D personality, experience negative emotions and inhibit the expression of emotion/behaviour.…”
mentioning
confidence: 99%
“…There have been few studies reported in the cardiac population, for example, clustering symptoms to predict risk of myocardial infarction 5,6 or profiling patients with ischemic coronary heart disease to examine how profiles differ on health-related quality of life (HRQoL). 4,8 This analysis was specifically conducted to contribute to the literature regarding patients' recovery after CABS by profiling patients on their symptoms at time of hospital discharge as a mechanism to identify those patients at risk for impaired physical functioning and physical activity at 6 weeks and at 3 and 6 months after surgery.…”
mentioning
confidence: 99%